PERSEPSI DAN KONTRIBUSI PEREMPUAN PADA USAHA BUDIDAYA RUMPUT LAUT DI DESA LANGGAPULU KECAMATAN KOLONO TIMUR - Muhammad Aras Saputra; Anas Nikoyan; Rosmawaty Rosmawaty (Universitas Halu Oleo, 2022)
This study aims to: Knowing women's perceptions of seaweed business in Langgapulu Village, Kolono Timur District, South Konawe Regency; Knowing the contribution of women to the allocation of time and income for women in seaweed farming. The population in this study were all female seaweed cultivators in Langgapulu Village, East Kolono District, South Konawe Regency. Respondents in this study used purposive sampling method, namely the technique of determining respondents based on considerations to explore aspects. The results of this study indicate that the perceptions of women cultivators in seaweed cultivation activities in Langgapulu village, seen from the cognitive, affective, and conative components, have been said to be good because they basically cultivate seaweed based on hereditary experiences that are in accordance with recommendations from fisheries extension, The amount of time allocation contribution for women seaweed cultivators is 52,46% and the contribution of women's income in seaweed farming is Rp.6.125.000 if the percentage is 50%.